Gene transfer to promote cardiac regeneration. (1st November 2016) - Collesi, Chiara; Giacca, Mauro
Abstract: There is an impelling need to develop new therapeutic strategies for patients with myocardial infarction and heart failure. Leading from the large quantity of new information gathered over the last few years on the mechanisms controlling cardiomyocyte proliferation during embryonic and fetal life, it is now possible to devise innovative therapies based on cardiac gene transfer. Different protein-coding genes controlling cell cycle progression or cardiomyocyte specification and differentiation, along with microRNA mimics and inhibitors regulating pre-natal and early post-natal cell proliferation, are amenable to transformation in potential therapeutics for cardiac regeneration. These gene therapy approaches are conceptually revolutionary, since they are aimed at stimulating the intrinsic potential of differentiated cardiac cells to proliferate, rather than relying on the implantation of exogenously expanded cells to achieve tissue regeneration. For efficient and prolonged cardiac gene transfer, vectors based on the Adeno-Associated Virus stand as safe, efficient and reliable tools for cardiac gene therapy applications.